Pharmacists as Strategic Leaders of Manufacturing Pharmaceutical Companies with Operations in South Africa - Nsovo Nyeleti Mayimele; Patrick Hulisani Demana; Mothobi Godfrey Keele (Business Ethics and Leadership, 2023)
The manufacturing sector of the pharmaceutical industry has faced criticism for disparities in access to pharmaceuticals, especially within the context of past incidents and the COVID-19 pandemic. Balancing profitability with the public responsibility to produce affordable, safe and effective medicines is challenging. The World Health Organisation (WHO) recognises the significant role pharmacists play in discovering, manufacturing and dispensing medicines. Pharmacists are responsible for safeguarding pharmaceuticals at all levels of care and where medicines are used. The research aimed to assess the involvement of pharmacists in the strategic leadership of Multinational Pharmaceutical Companies (MPCs) operating in South Africa. The study assessed the presence of pharmacists, recognised as custodians of medicines, in the strategic leadership of pharmaceutical companies operating in South Africa but headquartered globally. A desktop review was done to assess the company profiles, including revenue, size, number of employees and professional backgrounds of the persons in strategic leadership, including board and executive levels. The pharmaceutical companies were headquartered in eleven countries across Asia (3), Africa (1), North America (1), and Europe (6). On average, these companies operated in 86.6 countries (SD ±46.2). The strategic leadership roles within MPCs were comprised of individuals with backgrounds in commerce, sciences, and engineering. Predominantly, professionals with backgrounds in commerce held significant representation in both board membership and executive leadership within these companies. Notably, only 3.2% (33 out of 1023) of leaders possessed a pharmacy qualification, with a mere 27% (9 out of 33) being female. This was the least represented professional background among the strategic leaders, and the likelihood was affected by gender. The pharmacists more likely to hold strategic positions were predominantly male, had additional qualifications, and were situated in specific countries like India and South Africa. Pharmaceutical companies are essential in producing medicines to address global healthcare needs, functioning as healthcare service providers. Strategic leaders in these companies guide the manufacturing sites' strategic goals of the companies. The study's outcomes revealed a restricted presence of pharmacists in leadership roles despite their typical responsibility for manufacturing sites. These pharmacists were often found to have limited authority and were excluded from pivotal decision-making processes, resulting in significant implications for patient welfare.
Keywords: I11; L65; P46; 330; Pharmaceutical industry; Pharmacists; Manufacturing; strategic leadership; listed companies; pharmacy leadership